Anticholinesterasic, Nematostatic and Anthelmintic Activities of Pyridinic and Pyrazinic Compounds - Valli, M. [UNESP]; Danuello, A. [UNESP]; Pivatto, M. [UNESP]; Saldana, J. C.; Heinzen, H.; Dominguez, L.; Campos, V. P.; Marqui, S. R. [UNESP]; Young, M. C. M.; Viegas, C.; Silva, D. H. S. [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Bentham Science Publ Ltd, 2011)
In the search for acetylcholinesterase inhibitors as a potential target for the discovery of anthelmintic drugs, a series of 27 pyridinic and pyrazinic compounds have been designed on the basis of molecular hybridization of two known AChE inhibitors, namely, tacrine and (-)-3-O-acetylspectaline, and on the concept of isosterism. The synthesized compounds generally presented moderate anticholinesterasic activities when compared with the positive control physostigmine, but one compound (ethyl 2-[(6-chloropyrazin-2-yl) sulfanyl] acetate, 11) exhibited an in vitro ability to immobilize the root-knot nematode Meloidogyne incognita that was highly comparable to that of the positive control Temik. Moreover, in anthelmintic assays against the gastrointestinal parasitic nematode Nippostrongylus brasiliensis (L4), some of the compounds, such as (6-chloropyrazin-2-yl) sulfanyl ethanol (32, EC(50) = 33 nM), presented activities that were considerably stronger than that of the positive control albendazole (EC(50) = 340 nM). In the light of the positive results obtained in the anthelmintic evaluations, the acute oral toxicity of the representative compound diethyl 2,2'-[(3-nitropyridine-2,6-diyl) bissulfanediyl] diacetate (7) was determined in rats, and the drug was shown to be non-toxic at a dose of 2000 mg/kg. These results, allied with the relatively simple structures of the active compounds and their facile synthesis, highlight their potential use as anthelmintic or nematicidic agents.
Keywords: Acetylcholinesterase inhibition; anthelmintic activity; nematicidic activity; pyridine derivatives; molecular hybridization; isosterism; Nippostrongylus brasiliensis; Meloidogyne incognita; natural products